Effect of microbial diversity and their functions on soil nutrient cycling in the rhizosphere zone of Dahongpao mother tree and cutting Dahongpao - Jia, Xiaoli; Hong, Lei; Wang, Yulin; Zhang, Qi; Wang, Yuhua; Jia, Miao; Luo, Yangxin; Wang, Tingting; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2025)
Dahongpao mother tree (Camellia sinensis) is nearly 400 years old and is the symbol of Wuyi rock tea. It is unclear whether the structure and function of the rhizosphere soil microbial community of Dahongpao mother tree (MD) and its cutting Dahongpao (PD) change after planting. In this study, macrogenomics was used to analyze the structure and function of rhizosphere soil microbial communities, as well as to explore their relationship with soil nutrient transformations in MD and PD tea trees. The results showed that pH, total nitrogen, total phosphorus, total potassium, available nitrogen, available phosphorus and available potassium were significantly higher in the rhizosphere soil of MD than in PD by 1.22, 3.24, 5.38, 1.10, 1.52, 4.42 and 1.17 times, respectively. Secondly, soil urease, sucrase, protease, cellulase and catalase activities were also significantly higher in MD than in PD by 1.25-, 2.95-, 1.14-, 1.23-, and 1.30-fold. Macrogenomic analysis showed that rhizosphere soil microbial richness and diversity were higher in MD than in PD. There were eight characteristic microorganisms that significantly differed between MD and PD rhizosphere soils, and the results of functional analysis showed that MD rhizosphere soil microorganisms had higher carbon, nitrogen, and phosphorus biotransformation capacity, were more conducive to the accumulation and release of nutrients in the soil, and were more conducive to the promotion of tea tree growth. The results of PLS-SEM equation analysis showed that characteristic microorganisms positively regulated soil microbial function (1.00**), enzyme activity (0.84*) and nutrient content (0.82*). It can be seen that the abundance of soil characteristic microorganisms in the rhizospehre soil of MD increased significantly compared with that of PD, prompting a significant enhancement of their corresponding functions, which was more conducive to soil improvement, increased soil enzyme activity, enhanced soil nutrient biotransformation, and then increased soil nutrient accumulation and effectiveness, and promoted the growth of tea trees. This study provides an important theoretical basis for microbial regulation of tea tree cuttings management.